2023
DOI: 10.1177/08445621221150946
|View full text |Cite
|
Sign up to set email alerts
|

New Graduate Nurses Navigating Entry to Practice in the Covid-19 Pandemic

Abstract: Background The Covid-19 pandemic has significantly impacted organizational life for nurses, with known physical and psychological impacts. New graduate nurses are a subset of nurses with unique needs and challenges as they transition into their registered nurse roles. However, this subset of nurses has yet to be explored in the context of the Covid-19 pandemic. Purpose To explore the experiences of new graduate nurses entering the profession in Ontario, Canada, during the Covid-19 pandemic approximately one ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 79 publications
3
17
0
Order By: Relevance
“…The responses of participants in our study were also similar to those reported by McMillan et al. (2023).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The responses of participants in our study were also similar to those reported by McMillan et al. (2023).…”
Section: Discussionsupporting
confidence: 91%
“…The pandemic resulted in many new nurse orientations being cut short, decreased educational opportunities in their workplaces, and limited employment opportunities (Jerome-D' Emilia et al, 2022;Kovancı & Özbaş, 2022). The responses of participants in our study were also similar to those reported by McMillan et al (2023).…”
Section: Discussionsupporting
confidence: 76%
“…Workplace wellness and support are key components of nurses' intention to stay at an organization 30 ; this is particularly true with novice nurses. 31 According to a recent Cochrane review exploring how nurse staffing models impact outcomes, most nurse outcome data came from observational rather than interventional studies, which limits the conclusive strength of their findings. 32 In addition, the authors commented on the heterogeneity of metrics across study settings.…”
Section: Discussionmentioning
confidence: 99%
“…Newly graduated nurses often experience a problematic developmental lag when entering the workforce in terms of functioning autonomously in caring for patients, as well as a lack of support from experienced nurses to accommodate their needs for skill development (e.g. clinical leadership, patient assessment, coping with emotional distress) (Kaldal et al, 2023a; Rush et al, 2019; McMillan et al, 2023). Newly graduated nurses are also working in increasingly complex and rapidly changing care environments, characterized by increasing patient acuity, high patient turnover, technological advancements and demanding workloads (Hallaran et al, 2023; Hussein et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, newly graduated nurses who feel less committed to the organization they work for are less motivated to pursue opportunities for professional development and growth (Zhai et al, 2023). Similarly, a lack of supportive educational environments and resources is also shown to adversely impact newly graduated nurses' commitment (McMillan et al, 2023; Rush et al, 2019). Supporting newly graduated nurses in developing and maintaining a strong commitment to being a nurse and to stay in their workplace, therefore, has the potential to promote high‐quality patient care and positive patient outcomes.…”
Section: Introductionmentioning
confidence: 99%